Parenting: Preparing the Adolescents - Yadav, Saroj (JOURNAL OF INDIAN EDUCATION, 2010)
Parenting can be the most rewarding work of adult life. Nothing brings more joy and pride than a happy, productive, and loving child. Each age and stage of a child’s development has specific goals and tasks. For infants, it is to eat, sleep, and explore their world. For adolescents, it is to become their own person with their own group of friends. The world is shrinking. The effect of globalisation, modernisation and the media boom has made the life of adolescent, their expectations and values very different from those of older generation. This is more so in respect of reproductive and sexual health. Understanding adolescence empathetically and helping them to develop life skills to deal with the conflicting situations occurring due to oneself, peer, society and parents is not only the responsibility of schools but also of the parents themselves.